What Drives Individual to Adopt Fintech: Extended TAM Model with Gender as Moderating Variable - Setiawan, Budi; Pandu, Nugraha Deni; Ahmed, Amanj Mohamed; Emilda, Emilda; Nathan, Robert Jeyakumar (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2023)
Access to financial services is pivotal in improving welfare, reducing poverty, and accelerating financial inclusion in the emerging nation. This study analyzes the factors that drive consumer adoption of fintech by extending the TAM model with financial literacy and government support, as well as gender as moderating variable. Data was collected from 397 respondents in Indonesia and analyzed using SmartPLS 3.0. The result shows that perceived usefulness, ease of use, financial literacy, and government support significantly affect the adoption of fintech. The moderation analysis reveals that men perceive usefulness as more important for fintech adoption and ease of use for women.